2019
DOI: 10.1093/cvr/cvz165
|View full text |Cite
|
Sign up to set email alerts
|

Targeting protein tyrosine phosphatase PTP-PEST (PTPN12) for therapeutic intervention in acute myocardial infarction

Abstract: Aims The myocardial ischaemia/reperfusion (I/R) injury is almost inevitable since reperfusion is the only established treatment for acute myocardial infarction (AMI). To date there is no effective strategy available for reducing the I/R injury. Our aim was to elucidate the mechanisms underlying myocardial I/R injury and to develop a new strategy for attenuating the damage it causes. Methods and results Using a mouse model est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…The mRNA expression of ERBB2 receptors was signi cantly down-regulated in the left ventricle of MI compared with the normal left ventricle [25]. PTP-PEST contributed to part of the damages resulting from myocardial I/R and Aurano n, potentially acting through the PTP-PEST-ERBB2 signalling axis, reduced myocardial I/R injury [61]. S100 proteins are Ca 2 +-binding proteins exclusively expressed in vertebrates in a cell-speci c manner and they might regulate a variety of functions acting as intracellular Ca 2 + sensors transducing the Ca 2 + signal and extracellular factors affecting cellular activity via ligation of a battery of membrane receptors [62].…”
Section: Discussionmentioning
confidence: 95%
“…The mRNA expression of ERBB2 receptors was signi cantly down-regulated in the left ventricle of MI compared with the normal left ventricle [25]. PTP-PEST contributed to part of the damages resulting from myocardial I/R and Aurano n, potentially acting through the PTP-PEST-ERBB2 signalling axis, reduced myocardial I/R injury [61]. S100 proteins are Ca 2 +-binding proteins exclusively expressed in vertebrates in a cell-speci c manner and they might regulate a variety of functions acting as intracellular Ca 2 + sensors transducing the Ca 2 + signal and extracellular factors affecting cellular activity via ligation of a battery of membrane receptors [62].…”
Section: Discussionmentioning
confidence: 95%
“…We explored the versatility of our B2H system by assessing its ability to detect the inactivation of several other disease-relevant PTPs. In short, we swapped out the gene for PTP1B with genes for PTPN2, PTPN6, or PTPN12; these enzymes are targets for immunotherapeutic enhancement 59 , the treatment of ovarian cancer 60 , and acute myocardial infarction 61 , respectively.…”
Section: Design Of Alternative Ptp-speci C Objectivesmentioning
confidence: 99%
“…Concerning glucocorticoids in systemic lupus erythematosus, evidence is more straightforward showing deleterious side effects in heart and vessels (Wu et al, 2016) and clinicians agree in minimizing or withdrawing glucocorticoid dosage whenever it is possible (Fanouriakis et al, 2019 (Au et al, 2011;Chu et al, 2013;Derk & Jimenez, 2007;Spethman et al, 2014;Ungprasert et al, 2014). In parallel, they exhibit significant microvascular dysfunction (MVD) which is responsible for multiple manifestations of this disease, such as Raynaud phenomenon, pulmonary artery hypertension or renal sclerosis (Faccini, Kaski, & Camici, 2016).…”
Section: Effect Of Systemic Lupus Erythematosus Treatment On Myocarmentioning
confidence: 99%
“…Very recently, it has been demonstrated that Auranofin, a drug being used in clinical practice for treating rheumatoid arthritis reduces infarct size and results in better cardiac function when it is administered in mice before reperfusion. The potential underlying mechanism may involve the protein tyrosine phosphatases (PTP)‐PEST‐ErbB‐2 signalling axis (Yang et al, 2019). In a mouse model of adjuvant‐induced arthritis, which mimics RA in humans, ischaemic preconditioning did not result in a significant reduction of myocardial necrosis area induced by 30 min of ischaemia and 60 min of reperfusion (Wojciechowska et al, 2013).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%